Students’ Perception on the Digital Storytelling App in Learning Recount Text - Endang Sulistianingsih; Nur Fitria Utami (English Language in Focus (ELIF), 2022)
Eighth grade students of SMPN 11 Tegal have already implemented digital storytelling in learning recount text. But the perception of learning is not yet known. therefore it is necessary to have research with the aim to describe the perceptions of eighth grade students on the use of digital storytelling in learning recount text in SMP N 11 Tegal. This research is a descriptive study with an approach quantitative. The method used is the survey method and cluster sampling method by randomly drawing lots. The research instrument used was a questionnaire with 19 statements. The research instrument trials were conducted on 20 eighth and eighth grade students of Tegal Middle School 11. Questionnaire is declared valid and reliable (r count = 0.444). The subjects were eighth E and eighth F grade students of Tegal Middle School with a total of 50 respondents. Data analysis techniques using descriptive statistical techniques in the form of descriptive and frequency distribution. Based on the results of the study showed that the perception of eighth grade students of SMPN 11 Tegal on learning recount text using digital storytelling was in the very positive category. This can be seen in the recount text variable as much as 67.6% (very positive), 29.2% (positive), 3.2% (negative), and no one has a very negative perception. In the digital storytelling variable as many as 67.66% (very positive), 32.67% (positive), 1.66% (negative), and no one had a very negative perception. On the variable speaking skills as much as 64% (very positive), 35% (positive), 1% (negative), and no one has a very negative perception